Recognition of B-Cell Epitopes of the 65 kDa HSP in Behçet's Disease - DİRESKENELİ, RAFİ HANER (Blackwell Publishing Ltd., 1996)
B-cell epitopes of the mycobacterial 65 kDa heat shock protein (HSP) were mapped in sera from patients with Behçet's Disease (BD). A series of 47 overlapping synthetic peptides (15ers) derived from the sequence of the Mycobacterium tuberculosis 65 kDa HSP was used in ELISA. Significant increases in IgA and IgG antibody levels were observed with peptides 111-125, 154-172 and 311-326 in sera from BD, compared with those from controls. Homologous peptides derived from the sequence of the human mitochondrial 60 kDa HSP were then examined. Peptides 136-150 and 336-351 showed comparable results to the homologous mycobacterial peptides 111-125 and 311-326, respectively. The B-cell epitopes defined in this investigation overlap with the T-cell epitopes the authors have previously reported in BD. Inhibition studies are consistent with the view that antibodies to each of the three B-cell epitope peptides represent a small proportion of the total B-cell epitope repertoire elicited by the 65 or 60 kD HSP. Sequential antibody studies suggest that IgA and IgG antibody titres to one or all three peptides tested may increase during exacerbations of ocular disease. The functional role of these antibodies needs to be determined, but the peptides may be involved in the immunopathogenesis of BD as they can induce experimental uveitis in Lewis rats, which is a principal manifestation of BD.